2013
DOI: 10.4414/smw.2013.13816
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome in patients younger than 30 years – aetiologies, baseline characteristics and long-term clinical outcome

Abstract: ACS in young patients is an uncommon condition with a variety of possible aetiologies and distinct risk factors. In-hospital and 5-year clinical outcome is satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 24 publications
6
46
0
20
Order By: Relevance
“…10,11 CAD is much less frequent in premenopausal women due to the effect of estrogen; as the protection from CAD is much less evident after menopause, the disease affects both sexes equally. 12 In a recent study however, researchers have found that young women who are current smoker and obese are more likely to suffer from ACS.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 CAD is much less frequent in premenopausal women due to the effect of estrogen; as the protection from CAD is much less evident after menopause, the disease affects both sexes equally. 12 In a recent study however, researchers have found that young women who are current smoker and obese are more likely to suffer from ACS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigated the rate of incidence, clinical and angiographic characteristics, and long-term clinical outcome of ACS in Swiss hospitals. Current smoking (81%) and dyslipidemia (59%) were the most common risk factors [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The primary cause of MI in both young adults and in older age groups is coronary artery atherosclerosis [2,10]. Choudhury and Marsh assessed atherosclerosis as the cause of 80% of MI in young individuals [3].…”
Section: Introductionmentioning
confidence: 99%